2019
DOI: 10.1002/chem.201903658
|View full text |Cite
|
Sign up to set email alerts
|

High‐Throughput Synthesis and Characterization of Aryl Silicones by Using the Piers–Rubinsztajn Reaction

Abstract: Arylsilicones are widely exploited for their thermal and optical properties. The creation of phenylsilicone elastomers with specific physical properties is typically done by a “one‐off” formulation and test process. Herein, it is demonstrated that high‐throughput synthesis methods can be used to rapidly prepare a series of arylsilicone elastomers and then the relative impact of different aryl groups on their physical properties is assessed. Aromatic groups were incorporated into polydimethylsiloxane (PDMS) ela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…We have previously demonstrated the use of PR chemistry in coupling triarylamines to siloxane oligomers or polymers for the generation of new materials. This type of chemistry has also been used to make many other functional materials such as siloxane-based foams, , surfactants, cross-linkers with lignin, elastomers, , polymers, dendrons, , and other unique cyclic macrocycles . The PR reaction uses tris­(pentafluorophenyl)­borane as an organic Lewis acid catalyst, coupling a Si–H bond to an oxygen-based nucleophile and then forming a Si–O bond. Examples of oxygen-based nucleophiles include hydroxy (−OH) and ether (−OR) groups and yield hydrogen (H 2 ) or methane (CH 4 ) as a byproduct.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated the use of PR chemistry in coupling triarylamines to siloxane oligomers or polymers for the generation of new materials. This type of chemistry has also been used to make many other functional materials such as siloxane-based foams, , surfactants, cross-linkers with lignin, elastomers, , polymers, dendrons, , and other unique cyclic macrocycles . The PR reaction uses tris­(pentafluorophenyl)­borane as an organic Lewis acid catalyst, coupling a Si–H bond to an oxygen-based nucleophile and then forming a Si–O bond. Examples of oxygen-based nucleophiles include hydroxy (−OH) and ether (−OR) groups and yield hydrogen (H 2 ) or methane (CH 4 ) as a byproduct.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, developing Si-HBPs via simple, rapid and mild synthetic procedures is highly desirable. The Piers-Rubinsztajn (P-R) reaction, namely the condensation of alkoxysilanes with hydrosilanes, has rapidly developed since it was found in the 1990s [22,23], because this strategy is mild and provides a possibility for the controlled or precise synthesis of silicones, including small molecules, linear polymers, and crosslinked materials [24][25][26][27][28][29][30][31]. For example, the P-R coupling reactions of various organic tris(dimethylsiloxy)silane and trialkoxysilane compounds can generate a series of cyclic polysiloxanes with cyclotetrasiloxane subunits in a simple one-step synthesis [32].…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Brook and co-workers showed that the synthesis of siloxanes using this method can occur using a high-throughput strategy with the aid of a robot. 39 Many of the structures in Scheme 3 contain extra functionality in the form of substituted aryl groups or vinyl groups which allow for post-Piers-Rubinsztajn secondary reactions, e.g. curing the groups via heat-induced radical polymerization.…”
Section: Erin M Leitaomentioning
confidence: 99%